Franchising, Ownership, and Experience: A Study of Pizza Restaurant Survival - Kalnins, Arturs; Mayer, Kyle J. (Management Science, 2004)
We hypothesize that retail and service business units will enjoy reduced failure rates if affiliated with experienced multiunit owners and franchisors. Experience of individual owners and franchisees should result in knowledge that is tacit and idiosyncratic and thus primarily of value locally. Because franchisors typically codify knowledge gained from experience, we argue that units should benefit from both local and distant experience of their franchisor. Using Texan pizza restaurant failure data, we found that the units of all multiunit owners, franchised or not, benefited from their owner's local congenital experience, but not from distantly gained experience. Further, the franchisor's local experience reduced failure rates. Contrary to one hypothesis, franchisors' distant experience did not prove beneficial. In addition, a complementary effect was found for owner and franchisor congenital experience. These results highlight the continued importance of local experience, even among the most codified and standardized business organizations.